2017
DOI: 10.1111/rda.13016
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal or pathological findings? Morphofunctional characteristics of the equine endometrium during the autumn and spring transition

Abstract: The deep anoestrous phase in winter is part of the anovulatory season in mares and is bordered by the autumn and spring transitional periods (ATP/STP). To define an annual time span for effective prognostic biopsy sampling, the aim of this study was to provide a morphofunctional characterization of the endometrium during ATP and STP. To outline both transitional periods, endometrial specimens were taken in September, October and November (n = 76) as well as February, March and April (n = 184) with the requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Only during the physiological breeding season (15th March-15th September, in the northern hemisphere) are the behavioral, ovarian, and endometrial activities synchronized to allow a successful mating (Aurich, 2005;Sharp, 2011). Endometrial inactivity is commonly observed during winter anestrus and in the beginning of the transitional period in spring, whereas an irregular glandular differentiation may occur during the transitional cycles (Killisch et al, 2014). If these findings are diagnosed during the breeding season, they represent a pathological alteration associated with a permanent or temporary reduced fertility .…”
Section: Discussionmentioning
confidence: 99%
“…Only during the physiological breeding season (15th March-15th September, in the northern hemisphere) are the behavioral, ovarian, and endometrial activities synchronized to allow a successful mating (Aurich, 2005;Sharp, 2011). Endometrial inactivity is commonly observed during winter anestrus and in the beginning of the transitional period in spring, whereas an irregular glandular differentiation may occur during the transitional cycles (Killisch et al, 2014). If these findings are diagnosed during the breeding season, they represent a pathological alteration associated with a permanent or temporary reduced fertility .…”
Section: Discussionmentioning
confidence: 99%
“…Functional disturbances may lead to permanent or temporary infertility depending on the individual cause (Schoon et al 1999b, Ellenberger et al 2005. Their prognostic significance during winter anoestrus (Aupperle et al 2003) and transition periods (Killisch et al 2017) is questionable whereas they are an important finding with impact on the fertility of the mare in the breeding season. There is no association between the occurrence of functional disturbances and the age of the mare (Schoon et al 1999b, 2000, Schilling 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the hypothalamic-pituitary gland-ovarian axis gradually increases during STP and decreases during ATP [35]. Accordingly, biopsies collected during early, mid-, and late STP show a gradual increase in glandular activity [9], whereas those obtained during early, mid-, and late ATP display a successive decrease in glandular activity [9]. An irregular differentiation during the transitional periods is observed in 22-30% of the biopsies and is regarded as a physiological finding likely evoked by irregular ovarian cycles [9].…”
Section: Endometrial Histology and Influencing Factorsmentioning
confidence: 98%
“…Endometrial diseases of mares are an important cause of subfertility. These include endometrosis, endometritis, glandular differentiation disorders, and angiosis (synonym: angiosclerosis) [1][2][3][4][5][6][7][8][9]. Individual mares often display the concurrent presence of several endometrial diseases [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation